2008
DOI: 10.1165/rcmb.2007-0368oc
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus-8 Infection of Primary Pulmonary Microvascular Endothelial Cells

Abstract: Human herpesvirus-8 (HHV-8) is the causative agent of Kaposi's sarcoma and is associated with the angioproliferative disorders primary effusion lymphoma and multicentric Castleman's disease. Evidence of HHV-8 infection within the pulmonary vasculature of patients with idiopathic pulmonary arterial hypertension (IPAH) has been described. We hypothesize that HHV-8 infection of pulmonary microvascular endothelial cells results in an apoptotic-resistant phenotype characteristic of severe pulmonary arterial hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
0
21
1
Order By: Relevance
“…Although we found the LANA-1 protein in the lungs of patients with IPAH [82], the work is controversial and has not been supported by serologic studies, although one other group found similar LANA staining in a similar percentage of lungs from patients with IPAH [83]. The work by Bull et al [90] and Durrington et al [93] regarding the consequences of HHV-8 infection of endothelial cells suggests that HHV-8 is a potential viral cause of PAH [90,93]. That HHV-8 is not found in PAH in other regions does not negate its possible role in the development of PAH.…”
Section: Expert Commentarycontrasting
confidence: 52%
See 1 more Smart Citation
“…Although we found the LANA-1 protein in the lungs of patients with IPAH [82], the work is controversial and has not been supported by serologic studies, although one other group found similar LANA staining in a similar percentage of lungs from patients with IPAH [83]. The work by Bull et al [90] and Durrington et al [93] regarding the consequences of HHV-8 infection of endothelial cells suggests that HHV-8 is a potential viral cause of PAH [90,93]. That HHV-8 is not found in PAH in other regions does not negate its possible role in the development of PAH.…”
Section: Expert Commentarycontrasting
confidence: 52%
“…Bull et al recently used an in vitro model of HHV-8 infection of pulmonary endothelial cells and found that not only can HHV-8 infect primary human pulmonary microvascular endothelial cells, but that infection leads to alterations of gene and protein expression [90]. BMPR1a and BMP4 -both part of the TGF-b signaling pathway -are decreased following HHV-8 infection.…”
Section: Hhv-8 and Pahmentioning
confidence: 99%
“…Recently, conclusive evidence that idiopathic PAH pulmonary artery EC have a hyperproliferative apoptosisresistant phenotype compared with cells from control lungs has been shown using cell proliferation, DNA synthesis, and the evaluation of cell death pathways (42). Likewise, human herpes virus 8 (HHV-8) infection of pulmonary microvascular EC results in an apoptotic-resistant phenotype characteristic of severe PAH (43), although it is unclear whether HHV-8 has a pathogenetic role in idiopathic PAH (44)(45)(46). Moreover, dysfunctional endothelial progenitor cells, which are hyperproliferative with impaired ability to form vascular networks, are involved in the vascular remodeling associated with PAH (47).…”
Section: Smc and Ec In The Many Forms Of Pahmentioning
confidence: 99%
“…Several viral infections, including HIV, HHV-8, and hepatitis B and C, are implicated in producing increased PAH incidence and prevalence [109][110][111][112][113][114]. It is estimated that HIV infection increases the prevalence of PAH approximately 2500-fold [110].…”
Section: Principlementioning
confidence: 99%